Pengembangan Model Pembelajaran Better Plan untuk Pembelajaran di SD - Satriya, Sega; Sutomo, Dr; Sarwono, Ridha; Rinenggo, Alil (Faculty of Teacher Training and Education of Undaris, 2024)
This research aims to develop an interactive, differentiated, technology-based learning model and shared learning experiences (Better Plan) for elementary school learning. This research also aims to validate the model. This research uses the ADDIE development model which includes analysis, design, development, implementation and evaluation stages. The data collection technique is carried out through filling out a questionnaire. Based on the research results, it was found that (1) the Better Plan learning model was successfully developed by researchers by developing a learning model based on interactive technology, differentiated learning, and shared learning experiences for elementary school learning; (2) the Better Plan learning model is a valid tool and can be used for elementary school learning. This model has been validated by two learning experts, obtaining results of 95% and 94% in the very valid category. Thus, it is hoped that this research can make a contribution to the field of education and provide solutions that can be used by teachers in facing future learning challenges.Keywords: Learning loss, learning model, better plan